Transpersonal Psychology: Takhalli and its Relation to the Concept of the Soul - Alfian Dewan Adhayuda Prabowo; Khoiruddin Bashori (Al Misykat : Journal of Islamic Psychology, 2023)
Let us stay away from the nature and behavior of hubb al dunya. Hubb al dunya is love of the world in excess. This can have a bad impact because it causes heart and soul disease. This article aims to find the relationship between takhalli and the concept of soul. The approach used is a qualitative method with literature study research. The results showed: takhalli is withdrawing from the world by eliminating outward and spiritual immorality. Disobedience can be removed by purifying the heart through repentance, zuhud, and muhasabah. While in the concept of the soul, evil behavior occurs because humans prioritize the lawwamah and ammarah nafs. The relationship between takhalli and the concept of soul lies between the relationship of the heart and soul. The heart connects the spirit and the soul, even the heart is called the deepest recess of the soul.